2012
DOI: 10.1021/ic300694m
|View full text |Cite
|
Sign up to set email alerts
|

Cyclometalated Iridium(III) Complexes Containing Hydroxide/Chloride Ligands: Isolation of Heterobridged Dinuclear Iridium(III) Compounds Containing μ-OH and μ-Pyrazole Ligands

Abstract: The reaction of the cyclometalated chloro-bridged iridium(III) dimers [(ppy)(2) Ir(μ-Cl)](2) (ppyH = 2-phenyl pyridine) and [(tpy)(2)Ir(μ-Cl)](2) (tpyH = 2-p-tolylpyridine) with 3,5-diphenylpyrazole (Ph(2)PzH) in the presence of sodium methoxide resulted in the formation of heterobridged dimers [(ppy)(2)Ir(μ-OH)(μ-Ph(2)Pz)Ir(ppy)(2)] (1) and [(tpy)(2)Ir(μ-OH)(μ-Ph(2)Pz)Ir(tpy)(2)] (2). Interestingly, the reaction of [(ppy)(2)Ir(μ-Cl)](2) with 3(5)-methyl-5(3)-phenylpyrazole (PhMePzH) afforded both a heterobrid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 55 publications
1
21
0
Order By: Relevance
“…1, 2 and 3 ( Figure 1). [18][19][20][21][22][23][24][25][26][27][28][29] Consequently, for luminescence applications research has primarily concentrated on monoiridium complexes. 30,31 Nevertheless, the study of phosphorescent diiridium complexes is a rapidly expanding topic and a range of complexes with various conjugated bridging ligands have been reported to possess efficient photo-(PL) and electroluminescence (EL).…”
Section: Introductionmentioning
confidence: 99%
“…1, 2 and 3 ( Figure 1). [18][19][20][21][22][23][24][25][26][27][28][29] Consequently, for luminescence applications research has primarily concentrated on monoiridium complexes. 30,31 Nevertheless, the study of phosphorescent diiridium complexes is a rapidly expanding topic and a range of complexes with various conjugated bridging ligands have been reported to possess efficient photo-(PL) and electroluminescence (EL).…”
Section: Introductionmentioning
confidence: 99%
“…In the last years, we described the syntheses of several cyclometalated M III complexes of the elements rhodium and iridium,5 and particularly, we reported the synthesis and structural characterization of some complexes containing several biomolecules as the ancillary ligands 6. Most of the known cyclometalated Rh and Ir complexes are mononuclear, and except for the chloride‐bridged dimers formed from high‐temperature reactions of the corresponding metal(III) chlorides and the cyclometallating ligand, rather few di‐ or oligomeric complexes of this type have been reported 710. This can be mainly attributed to the opinion that such dinuclear compounds are not suitable for opto‐electronical devices, a view that might have to be revised according to some recent findings 8.…”
Section: Introductionmentioning
confidence: 99%
“…This can be mainly attributed to the opinion that such dinuclear compounds are not suitable for opto‐electronical devices, a view that might have to be revised according to some recent findings 8. With Ir III , so far neutral NN ligands of the 4, 4'‐bipyridyl‐ type as well as anionic ligands, such as pyrazole, cyanide, and cyanate have been used as the bridging units 710. With cyclometallated Pd II complexes a series of anionic imidato ligands have been shown to act as N, O‐bridging units, [11, 12] while there seem to be no reports of the closely related amidato ligands as bridging groups with cyclometallated complex fragments.…”
Section: Introductionmentioning
confidence: 99%
“…[1b, 3-5] Cyclometalated iridium(III) complexes are widely exploited because of their excited-state lifetimes on the microsecond time scale, high quantum yields, good thermal and chemical stability, and tunability of the emission color. [6][7][8][9][10] In this context, the prototype complex is fac-[Ir(ppy) 3 ] (ppy = 2-phenylpyridine).The photoluminescence quantum yields of dinuclear metal complexes [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25] are usually considerably lower than those of their mononuclear analogues [12,14,23,24] (although there are exceptions), [25] leading to the established view that dinuclear complexes give poor device performance. [26,27] For example, the quantum yield of the bis(m-Cl) bridged dimer [{Ir(ppy) 2 Cl} 2 ] (1) is only 0.5 %, [11] whereas that of fac-[Ir(ppy) 3 ] is 40(AE0.1) % (both in toluene).…”
mentioning
confidence: 99%
“…We are not aware of a previous computational study on diiridium complexes where the bridge has been shown to be heavily involved in the HOMO: Typically, either the LUMO involves bridge character, [16,18,23,32] or the bridge is not involved in either frontier orbital. [19,24] The photophysical data for 2, 3, and 4 are shown in Figures S8 and S9 and Tables S3 and S4; data for [Ir(ppy) 3 ] and 1 obtained under directly comparable conditions are included for comparison. The PL emissions of 3 and 4 at 521 nm and 523 nm are featureless, which indicates a dominant 3 MLCT contribution and little signature of 3 LC contribution.…”
mentioning
confidence: 99%